Quantifying the impact of COVID–19 preventive measures on traffic in the State of Qatar. (March 2021) - Muley, Deepti; Ghanim, Mohammad Shareef; Mohammad, Anas; Kharbeche, Mohamed
Abstract: Ever since the beginning of 2020, the mobility of people and goods all over the world has been extremely limited as a result of movement restrictions imposed by local authorities as part of several other efforts to stop the wide spread of COVID–19 pandemic. The Supreme Committee for Crisis Management in the State of Qatar adopted the policy of incremental preventive measures that were adjusted based on the pandemic status. These actions involved several restrictions, aiming a balance between reducing the pandemic spread and the typical daily activities disturbance. This paper assesses the impact of pandemic response measures on traffic mobility by quantifying the holistic impact of the incremental measures at different stages on traffic volumes and traffic safety. Daily traffic counts from 24 intersections were collected every 15-min for several days, representing the traffic before and after implementing each preventive measure. Besides, a screenline was used to represent the traffic entering and leaving the Central Business District (CBD) in the City of Doha. The results show that the daily traffic demand distribution over the course of day was not affected by those preventive measures. However, an overall demand reduction of 30% in baseline traffic was observed for all studied intersections and the screenline when all preventive measures were active. Moreover, the analysis of traffic violations and the total crashes indicated a drop of 73% and 37% respectively. The results from this assessment will assist decision and policy makers, and planners to prioritize traffic management actions for future needs. Further, the findings can also be utilized for mega–event traffic management in the post-COVID era, such as FIFA World Cup 2022 and 2030 Asian Games. Highlights: Mobility restrictions didn't change hourly distribution of traffic over the day. Total traffic dropped by 30% after implementtations of preventive measures. Complete movement restrictions resulted in 73% decrease in traffic violations. All preventive measures reduced total traffic crashes by about 37%. Phase 1 easing in movement restrictions increased violations and fatalities.